Analysis of the Free Nutritious Food Program (MBG) in Addressing Stunting Among Lower-Grade Students at SDN 042 Tarakan - Muh. Zefri Awal (CV. SAMODRA INSAN PENA, 2025)
Stunting remains a major nutritional challenge affecting children in many developing countries, including Indonesia. The Free Nutritious Food Program (MBG) implemented at SDN 042 Tarakan aims to address this issue by providing nutrient-dense meals to lower-grade students (grades 1–3). This qualitative study seeks to examine the effectiveness of the MBG program in improving students’ nutritional status and reducing stunting cases. Data were gathered through semi-structured interviews, focus group discussions (FGDs), participatory observations, and document analysis involving six homeroom teachers, the school principal, the MBG coordinator, and parents. The findings reveal notable improvements in students’ weight and height after participating in the program. Most students developed healthier eating habits, although challenges remain concerning the consistency of these habits at home. The study also highlights logistical and budgetary constraints that hinder optimal program implementation. Despite these limitations, the MBG program demonstrates strong potential in enhancing students’ health and overall well-being. Further research using quantitative methods is recommended to assess the long-term impact of MBG and its scalability to other schools facing similar nutritional issues